2019
DOI: 10.1002/aenm.201901213
|View full text |Cite
|
Sign up to set email alerts
|

Construction of CoP/NiCoP Nanotadpoles Heterojunction Interface for Wide pH Hydrogen Evolution Electrocatalysis and Supercapacitor

Abstract: Constructing well defined nanostructures is promising but still challenging for high‐efficiency catalysts for hydrogen evolution reaction (HER) and energy storage. Herein, utilizing the differences in surface energies between (111) facets of CoP and NiCoP, a novel CoP/NiCoP heterojunction is designed and synthesized with a nanotadpoles (NTs)‐like morphology via a solid‐state phase transformation strategy. By effective interface construction, the disorder in terms of electronic structure and coordination enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
142
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 309 publications
(155 citation statements)
references
References 56 publications
6
142
0
Order By: Relevance
“…[ 51–53 ] For P 2p 1/2 spectrum (Figure 3f), the peak at the binding energy of 129.9 eV corresponds to P 2p 1/2 , which is the characteristics of phosphorus species. [ 19,29 ] Meanwhile, a predominate peak of oxidized phosphorus species located at the binding energy of 133.5 eV is also observed. [ 29,54 ] Notably, the binding energies of nickel species and cobalt species in the NiCoP nanosheets positively shift as respect to that of metallic nickel (852.6 eV) and cobalt (778.2 eV), respectively, whereas the peak of phosphorus species shifts to lower binding energy compared with phosphorus element (130.2 eV).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 51–53 ] For P 2p 1/2 spectrum (Figure 3f), the peak at the binding energy of 129.9 eV corresponds to P 2p 1/2 , which is the characteristics of phosphorus species. [ 19,29 ] Meanwhile, a predominate peak of oxidized phosphorus species located at the binding energy of 133.5 eV is also observed. [ 29,54 ] Notably, the binding energies of nickel species and cobalt species in the NiCoP nanosheets positively shift as respect to that of metallic nickel (852.6 eV) and cobalt (778.2 eV), respectively, whereas the peak of phosphorus species shifts to lower binding energy compared with phosphorus element (130.2 eV).…”
Section: Resultsmentioning
confidence: 99%
“…The negatively charged P atoms with strong electrostatic affinity can effectively capture protons, thereby promoting hydrogen production. [ 3,18,19 ] The catalytic activity of Ni x Co y P z is closely related to its surface properties and electronic structures, and can be improved by increasing the quantity of exposed active sites and optimizing its electronic structures by rationally tuning the morphology, surface area, defects and composition of Ni x Co y P z . [ 20–26 ] For example, Liu and co‐workers adopted controllable oxygen doping strategy to obtain an efficient NiCoP electrocatalyst with a hydrogen adsorption energy close to zero and abundant exposed active sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Most of the reported heterostructures show welldefined nanostructures, substantially exposing active sites, which can offer more adsorption sites for hydrogen intermediates. Lin et al [123] recently reported CoP/ NiCoP nanotadpoles (NTs)-like heterojunction ( Fig. 7k and l) for efficient electrocatalytic HER over a wide pH range ( Fig.…”
Section: Design and Engineering On Heterointerfacesmentioning
confidence: 99%
“…The electronic redistribution can be well reflected by the XPS, especially the synchrotron-radiation-based X-ray absorption spectroscopy (XAS). Recent studies suggested that the formation of the heterointerfaces in heterostructured Ni/NiCoP NHs and CoP/ NiCoP NTs can tune the electronic structures of the catalysts, thus promoting the HER process [123,124].…”
Section: Design and Engineering On Heterointerfacesmentioning
confidence: 99%